FACTORS INFLUENCING TI-IE DECISION -MAKING OF USING XL CELLULAR SERVICES (A STUDY AT XL CELLULAR USERS IN RURAL AREAS OF CENTRAL LOMBOK REGENCY) - Silvia Herlina (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
The use of mobile services as a medium of communication showed increasing trend over time in the community. it also affects the changes in their behavior patterns. especially people who want the ease of communicating and getting information.  The problem formulated in this study is: what factors are influencing the decision-making of buyers of mobile services XL (study of mobile users XL in rural areas of Central Lombok district). seen from the aspects of individual consumers. environmental aspects and marketing stimuli aspects. and which of these factor dominantly influence the decision on the purchase of XL's mobile products.  This research is the associative / relationship study described through quantitative research approach to determine the effect of variable on the number of XL product user services in rural areas of central Lombok regency. Methods of sampling used is non probabiliy sampling. While the sampling technique is accidental sampling. The total number of sample is 100 people. There are 13 research variables. Thc variable is measured with Likert scale. Hypothesis testing used is multiple linear regression analysis through F test and T test with confidence level at 95% (a=0,05). The Results of partial testing of the nine factors that have significant influence show that simultanously consumers need (X1). consumers income (X2). the influence of family / neighbors (X4). consumers social interaction (X5). recomendation of consumers' friends (X6). price of XL credits (X8), quality of XL cellular service (X9). the availability of the service center of XL cellular (X I 0) and the availability of stores or vendors that sell cellular services XL (X 12) affect the decision of XL cellular services in Central Lombok Regency. meanwhile, the availability of the service center of XL is the most dominant factor.  From the results of this study. it is suggested that the marketers pay attention on marketing stimuli factors, in particular the availability of the service center as a consideration in formulating marketing strategic. and also for fellow researchers to conduct research on consumer behavior related to the their needs and desires. Keyword : changing patterns of behavior, individual aspects of consumer, environmental aspects, aspects of marketing stimuli, decisions on purchasing XL mobile services, availibility of service centers, needs and desires.